1997
DOI: 10.1002/chem.19970030615
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Mono‐ and Multilayer Self‐Assemblies of Oligothiophenes at the Air–Water Interface

Abstract: Abstract:The formation of Langmuir monolayers at the air-water interface has long been believed to be limited to amphiphilic molecules containing a hydrophobic chain and a hydrophilic headgroup. Here we report the formation of crystalline mono-and multilayer self-assemblics of oligothiophenes, a class of aromatic nonamphiphilic molecules, selfaggregated at the air-water interface. As model systems we have examined the deposition of quaterthiophene ( S , ) , quinquethiophene (SJ, and sexithiophene (S,) from chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…In recent years, quantum dots were prepared mainly in matrices and also as self-assembled structures, such as reverse micelles, [10] zeolites, [11] polymers, [12] self-assembled monolayers, [13] biopolymers, [14] layered metal phosphonates, [15] and Langmuir±Blodgett (LB) films. [16,17] In the preceding communication, [18] we reported that spreading of tetracosanedioic acid HOOC(CH 2 ) 22 COOH (C 24 diacid) on surfaces of aqueous solutions containing di- …”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent years, quantum dots were prepared mainly in matrices and also as self-assembled structures, such as reverse micelles, [10] zeolites, [11] polymers, [12] self-assembled monolayers, [13] biopolymers, [14] layered metal phosphonates, [15] and Langmuir±Blodgett (LB) films. [16,17] In the preceding communication, [18] we reported that spreading of tetracosanedioic acid HOOC(CH 2 ) 22 COOH (C 24 diacid) on surfaces of aqueous solutions containing di- …”
Section: Methodsmentioning
confidence: 98%
“…Recently, the formation at the air±water interface of crystalline monolayer and multilayer films obtained from symmetric molecules with end groups equally hydrophobic or hydrophilic, such as long-chain linear fluorocarbons [14] and hydrocarbons, [15] oligothiophenes [16] (containing four, five, and six rings), and a,w-alkanediols, [17] has been reported. In these films at low surface pressure the long molecular axis is aligned either normal to the water surface or tilted by up to 40 from the normal.…”
mentioning
confidence: 99%
“…Charge carriers are trapped or scattered by defects and impurities in the accumulation region or at its interfaces. In addition, at such small thicknesses, due to the small size of the crystal and the proximity of the gate insulator interfaces, monolayers of small‐molecule organic semiconductors have a complex arrangement of molecules, often including different island morphologies and crystallographic structures than in thicker films 7, 8. The crystallographic differences lead to different intrinsic overlap of the molecular orbitals of adjacent molecules and thus to different hole transport characteristics 9.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic Ni 3 (HITP) 2 nanoparticles float on the water surface, which acts as a “smooth substrate”, and consequently the nanoparticles closely pack to form a nanometer-thick uniform layer due to the interface-confining effect (Figure S1). , After the air–liquid interface is fully covered with this Ni 3 (HITP) 2 layer, the MOF membrane probably forms through continuous assembly of organic HITP components and nickel ions in the solution onto the Ni 3 (HITP) 2 layer at the MOF–solution interface. The formation of the membrane at the interface could be observed even by the naked eye.…”
mentioning
confidence: 99%
“…Herein we demonstrate an air−liquid interfacial method to prepare ultrasmooth and compact Ni 3 (HITP) 2 membranes S1). 20,21 After the air−liquid interface is fully covered with this Ni 3 (HITP) 2 layer, the MOF membrane probably forms through continuous assembly of organic HITP components and nickel ions in the solution onto the Ni 3 (HITP) 2 layer at the MOF−solution interface. The formation of the membrane at the interface could be observed even by the naked eye.…”
mentioning
confidence: 99%